Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C−F and S−F Bond Activation. Issue 13 (9th February 2023) - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan
Abstract: A series of redox‐responsive ferrocenyl‐substituted boranes and boronic esters were synthesized. Oxidation of the ferrocenyl ligand to the ferrocenium resulted in a drastic increase in the Lewis acidity beyond the strength of SbF5, which was investigated experimentally and computationally. The resulting highly Lewis acidic boron compounds were used for catalytic C−F and S−F bond activation. Abstract : The oxidation of ferrocenyl‐substituted boranes and boronic esters allows for the straightforward synthesis of strong boron‐centered Lewis superacids. The Lewis superacids were characterized by NMR, XRD and FIA computation. The ferrocenium‐substituted boranes were applied in catalytic C−F and S−F bond activations.